Debt Policy, Institutional Ownership, Company Values, and Assets Utilization as Intervening Variables in Manufacturing Companies in Indonesia - D. Lili Lestari; Mudjilah Rahayu (Jurnal Manajemen Teori dan Terapan | Journal of Theory and Applied Management, 2018)
Separation of functions between owners and management creates agency conflicts where the manager's decision is not necessarily in line with the owner. The manager no longer prioritizes the interests of the owner over his personal interests. Management as an insider effectively controls the company and knows more information than the owner as an outsider. In Asian countries, there is a tendency for majority ownership to take control in management. So that the agency conflict that occurs is no longer pure between managers and capital owners, but between majority and minority shareholders. This management system allows for expropriation by majority shareholders against minorities. The control mechanism is needed to suppress agency conflicts that exist within the company so that shareholders remain prioritized over the manager's personal interests.This study uses a sample of 123 manufacturing companies listed on the Indonesia Stock Exchange in 2013-2016. The results of the study show that debt has a significant negative effect on the utilization of assets and company value. While institutional ownership has a significant positive effect on asset utilization and company value.